Modelação das taxas de mortalidade associadas a hábitos alimentares nos municípios portugueses -uma análise exploratória utilizando geographically weighted regression - Ramos, Adriana Loução Guerreiro (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management